TINJAUAN YURIDIS MENGENAI PENERAPAN UNDANG-UNDANG NOMOR 30 TAHUN 2009 TENTANG KETENAGALISTRIKAN TERHADAP PENYEDIAAN TENAGA LISTRIK DAN PENGELOLAAN IURAN LISTRIK RUMAH SUSUN DI Indonesia (Studi Kasus Terhadap Tiga Apartemen Di Jakarta) - Haris Candra (Program Magister Ilmu Hukum Universitas Pancasila, 2018)
Limited land in big cities make business developments flats and apartments increasedsharply, this has an influence on the demand for electricity usage increases. On theother side, PT. PLN (Persero) has not been able to supply power directly to the unithousing project but only reached the main substation, then manager of flats distributeelectric power obtained from PLN through the substation flats to each apartment unit. Itis also related to the billing of electricity cost is PLN submit a bill to the manager, thenthe manager of the apartment to collect electricity dues from residents and owners of theunit. In the collection of the license fee, the manager also divide the other expenses thatare used for the mutual benefit proportionally. These conditions make the occupants andowners of units accused managers inflate electricity rates, as happened to the PPRS andManagement Agency Apartment Mediteramia Marina Residence, ApartmentMediterania Palace Residence and Apartments Gading Mediterania which have beenreported to the Party Police with allegations have been violating Article 49 Paragraph(1) and (2) of Law No. 30 Year 2009 on Electricity